Processing Effect on Phytic Acid and Inorganic Phosphorus Content of Soybean (Glycine max, Brown var.) - Rijal, Somkanta; Adhikari, Babita (Journal of Food Science and Technology Nepal, 2014)
The objective of this research was to study the effect of some processing methods on phytic acid (a prominent anti-nutritive substance) and inorganic phosphorous content of the king legume soybean. The processing treatments viz. soaking and subsequent germination; kinema fermentation and heating were applied. It was observed that soaking for 12 hrs at room temperature under citric acid solution, distilled water and sodium bicarbonate solution significantly (p <0.05) lowered the phytic acid content of soybean by 7.99%, 6.38% and 7.20% respectively and also correspondingly lowered the inorganic phosphorous by 21.8%, 27.55% and 30.75% . Maximum destruction of phytic acid (35.1% reduction) occurred during germination for 120 hrs in 0.1% citric acid solution. This was further confirmed by increase of inorganic phosphorous content (196.22%) in corresponding treatments. A 46.07% significant reduction (p < 0.05) of phytic acid content over the control was noticed after 72 hrs of kinema fermentation. On the same interval, inorganic phosphorous content also significantly increased by 180%. Autoclaving was found more effective than dry heating and boiling also could reduce the phytic acid content of soybean. Autoclaving (121ºC for 15 min), dry heating (200ºC for 5 min) and boiling (100ºC for 30 min) significantly lowered (p< 0.05) soybean phytate by 20.76%, 12.84% and 14.84% respectively. In other hand, inorganic phosphorous content were increased significantly by 80.56%, 43.8% and 63.55% at the same time. DOI: http://dx.doi.org/10.3126/jfstn.v7i0.11208 J. Food Sci. Technol. Nepal, Vol. 7 (102-106), 2012